Infrared receiver on transitions of electrons into an autolocalized state over a helium film on a structured substrate - Nikolaenko, V.A.; Pashchenko, A.G.; Bessmolny, Ya.Yu. (Radiotekhnika, 2017)
To construct an IR receiver, it is proposed to use a radiation-stimulated threshold transition from the state of the surface electron (SE) to the state of the surface anion (SA) over the helium film in the pores of the structured substrate. The transition depends on the thickness of the film, the electric field, and the density of the vapor phase. The electron mobility in the SE / SA transition corresponds to a theoretical analysis. The electrostatic model of a cylindrical pore in a longitudinal field demonstrates the preferential localization of electrons over the film inside the pore. The IR image is determined by the equipotential relief of the substrate, induced by the contrast of the conductivity of the electrons in the pores. The frequency range and sensitivity of the receiver are determined by the thermal sensitivity to the radiation of the pore walls and the operating temperature, reaching the quantum limit. The design and operation of the IR receiver are given.